2021
DOI: 10.1021/acssuschemeng.1c03420
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidation of Furfural to 2(5H)-Furanone and Maleic Acid over CuMoO4

Abstract: Green synthesis of high-value furanone derivatives and C 4 organic acids from renewable biomass is a promising yet challenging route. Herein, we report a suitable heterogeneous and recoverable bimetallic CuMoO 4 catalyst for the selective oxidation of furfural to 2(5H)-furanone and maleic acid (MAc). The resulting CuMoO 4 manifested excellent catalytic performance with a high furfural conversion of 99%, giving a 2(5H)-furanone yield of up to 66% or a MAc yield of over 74% by regulating the reaction conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Also, the work-up procedure of the latter is much simpler than that of the former. In terms of selectivity and yield, this photoenzymatic route appears to be superior to most of the previous processes, 18–25,28–30 due to its mild reaction conditions and inherently excellent selectivities of enzymes. Although the catalytic efficiency of the present route remains much lower than those of some thermocatalytic processs, 26,27 the former may have great environmental benefits, as it is free of both metal-based catalysts and organic solvents, and uses air as a green oxidant.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Also, the work-up procedure of the latter is much simpler than that of the former. In terms of selectivity and yield, this photoenzymatic route appears to be superior to most of the previous processes, 18–25,28–30 due to its mild reaction conditions and inherently excellent selectivities of enzymes. Although the catalytic efficiency of the present route remains much lower than those of some thermocatalytic processs, 26,27 the former may have great environmental benefits, as it is free of both metal-based catalysts and organic solvents, and uses air as a green oxidant.…”
Section: Resultsmentioning
confidence: 95%
“…Recent years have witnessed significant advances in the catalytic synthesis of MA from furfural. 2 Thermocatalytic furfural oxidation was a predominant route toward MA over metal, [18][19][20][21] acid, 22,23 and carbon catalysts 24,25 at elevated temperatures, but the selectivities were usually unsatisfactory (<70%), with the exception of limited examples. 26,27 In contrast, electrochemical oxidation of furfural occurred under milder conditions (e.g., 25 °C), affording MA with 65-84% selectivities.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al. showed that using a small amount of peroxymonosulfate as a radical initiator and CuMoO 4 as catalyst, 74 % yield of maleic acid can be obtained in an aqueous system [112] . In this reaction, 2(5H)‐furanone was proposed as the intermediate.…”
Section: Furfural To C4 Chemicalsmentioning
confidence: 99%
“…Further optimizations on the catalyst loading showed that an 8 wt% catalyst loading was enough to ensure quantitative conversion of a-AGL and a high isolated yield of GVL. The synthesized GBL and GVL were characterized using FTIR, 1 H NMR, and 13 C NMR spectroscopic techniques.…”
Section: Catalyst Evaluationmentioning
confidence: 99%
“…[10][11][12] FUR can be catalytically oxidized to 2-furanone using innocuous oxidants, such as gaseous O 2 and aqueous H 2 O 2 . 13,14 Catalytic hydrogenation of the olenic group in 2-furanone leads to g-butyrolactone (GBL). 15 GBL has applications as an industrial solvent, potential biofuel, and chemical feedstock in several industries, such as polymers, cosmetics, and pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%